Effect of Perceived Stress on Work-Life Balance among Married and Unmarried Working Women - Aarsha Ajayan (International Journal of Indian Psychȯlogy, 2022)
Perceived stress integrates feelings of loss of control and irregularity in one’s life, how often one has to make a pact with frustrations and hassles of daily life routine, the perceived anxiety from changes happening in one’s life and confidence in one’s ability to deal with different situations. The work-life balance is dependent on how well an individual can deal with the same. The premise in this research study was that perceived stress can be a major precursor in changing the work life balance. The aim of the research was to compare and explore the effect of perceived stress on work-life balance among married and unmarried working women. The tools used for assessment were Cohen’s Perceived Stress Scale (PSS) and Pareek & Purohit’s Work-Life Balance Scale (WLB). The study was conducted on 60 working women in which 30 were married and 30 were unmarried. The inferential statistics utilized to analyse the data was an Independent Sample t-test, to compare the difference between the sample groups and Pearson’s Product Moment Correlation with Simple Regression to explore the influence. The study reveals that a significant relationship exists between perceived stress and work-life balance wherein, perceived stress contributes significantly as a predictor of work life balance. Secondly, there were differences observed between the Work-life Balance and Perceived Stress among married and unmarried working women.